High-performance conductive silver paste and preparation method thereof

By introducing composite Ag/MXene micropowder into the conductive silver paste, the structure of poly-end alkenyl groups and mesh compounds is used to form a conductive material attached to the silver cluster, which solves the problem of insufficient performance of the existing conductive silver paste in flexible electronic equipment, and achieves high conductivity and excellent flexibility resistance.

CN119724683AActive Publication Date: 2025-03-28SICHUAN BOAOSHENG NEW MATERIALS CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411824507.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-03-28
Estimated Expiration
2045-01-22

AI Technical Summary

Technical Problem

The existing conductive silver paste is difficult to meet performance requirements in flexible electronic devices, especially in terms of mechanical properties and conductive properties, which limits the development of products such as wearable electronic devices and flexible displays.

Method used

The composite Ag/MXene micropowder is used as the conductive material, and the amine ester exchange reaction between diethyl iminodiacetate and diallylamine is formed to form a poly-terminal alkenyl compound, and the thiol-terminated small molecule reticular compound is added to the terminal double bond between ethylene dithiol and the intermediate to form a coating modifier. The coating modifier is uniformly spread on the MXene nanosheets, and forms silver cluster attachment through liquid phase reduction and calcination processes, improving conductivity and deformation recovery capabilities.

Benefits of technology

It realizes the low resistivity and excellent flexibility of conductive silver paste, maintains stable conductivity and has good deformation recovery capabilities, and is suitable for the application of flexible conductive materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119724683A_ABST
    Figure CN119724683A_ABST
Patent Text Reader

Abstract

The invention relates to high-performance conductive silver paste and a preparation method thereof, and belongs to the technical field of conductive paste. The conductive silver paste is prepared from the following components in parts by weight: 30 to 40 parts of micron silver powder, 1.9 to 2.7 parts of nano silver powder, 15 to 22 parts of Ag / MXene micro powder, 1.8 to 2.4 parts of thixotropic agent, 25 to 35 parts of organic resin, 1.3 to 1.8 parts of curing agent and 38 to 52 parts of solvent, according to the Ag / MXene micro powder, an MXene nanosheet serves as a carrier, a large number of silver clusters are loaded on the surface of the MXene nanosheet through chemical reduction and roasting processes, the contact probability of a lamellar structure and silver powder is increased, the conductivity of slurry after solidification is improved, the MXene lamellar layer provides good deformation recovery capacity, the surface of the MXene lamellar layer is provided with non-coated fine silver clusters, the buffering effect is achieved, and the conductivity of the slurry is improved. The structural stability is better in the deformation process, so that the stable conductivity is maintained, and the material has a profound application value in flexible conductive materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of conductive pastes, and in particular, relates to a high-performance conductive silver paste and a preparation method thereof. Background Art

[0002] Conductive silver paste is a special functional material with conductive and adhesive properties. It is made of a mixture of silver powder, adhesive resin, additives and solvents. It can be screen-printed according to the designed pattern and provides good conductivity after curing. It is widely used in various electronic products.

[0003] With the rapid development of the 5G information age, the electronic information industry has undergone a comprehensive innovation. Various new high-tech electronic products have gradually entered thousands of households and are widely favored by the public. At the same time, people have also put forward higher performance requirements for new electronic products, prompting electronic technology products to develop in the direction of lightness, thinness and flexibility; however, the mechanical properties and conductive properties of the conductive silver paste currently on the market that is compatible with flexible substrates are difficult to meet the performance requirements of flexible electronic devices, restricting the further development of wearable electronic devices, flexible displays and other products. The mechanical properties of silver paste are determined by the binding resin in it. The better the flexibility of the resin, the better the bending resistance of the silver paste. The selection of high-performance binding resin can improve the flexibility of the silver paste to a certain extent. As a conductive material, the different properties of silver powder such as morphology and particle size will affect the conductive properties of the silver paste. In order to obtain a conductive silver paste with high conductivity, silver powders of different morphologies and particle sizes are usually compounded to achieve high conductivity by reducing the contact resistance between the silver powders. Among them, the introduction of flaky conductive materials not only increases the contact area between the silver powders, but also forms a network structure in the silver paste, thereby increasing the flexibility of the silver paste, such as flaky silver powder, graphene and graphene derivatives. However, the bending recovery of flaky silver powder is poor, the hardness of the graphene sheet is large and the elastic modulus is extremely high, and the structure is easily destroyed during the flexible deformation process, which has a greater impact on the conductivity. Summary of the invention

[0004] In order to solve the technical problems mentioned in the background technology, the object of the present invention is to provide a high-performance conductive silver paste and a preparation method thereof.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A high-performance conductive silver paste, comprising, by weight:

[0007] 30-40 parts of micron-sized silver powder, 1.9-2.7 parts of nano-sized silver powder, 15-22 parts of Ag / MXene micropowder, 1.8-2.4 parts of thixotropic agent, 25-35 parts of organic resin, 1.3-1.8 parts of curing agent and 38-52 parts of solvent.

[0008] The Ag / MXene powder is prepared by the following method:

[0009] Step A1: premix diethyl iminodiacetate, diallylamine and anhydrous toluene under dry nitrogen protection, heat to 40-50°C, stir at 90-120 rpm, slowly add trimethylaluminum to react for 4-5 hours, then continue to heat and reflux for 1.5-2 hours, and quickly remove toluene by vacuum rotary evaporation to obtain an intermediate;

[0010] Furthermore, the feed ratio of diethyl iminodiacetate, diallylamine, trimethylaluminum and anhydrous toluene is 0.1 mol: 0.2 mol: 25-35 mg: 45-55 mL. Under the catalysis of trimethylaluminum, diethyl iminodiacetate and diallylamine undergo amine ester exchange to form a terminal polyolefin compound.

[0011] Step A2: Mix the intermediate, benzoin dimethyl ether and acetone, introduce nitrogen protection, heat to 45-55°C, apply 120-150 rpm stirring and 100-150 W / m 2 UV irradiation, intermittently adding ethanedithiol to react for 2.5-3.2 hours, and after the reaction, removing acetone by rotary evaporation to obtain a coated modifier;

[0012] Furthermore, the feed ratio of the intermediate, ethanedithiol, benzoin dimethyl ether and acetone is 0.1 mol: 0.28-0.32 mol: 60-80 mg: 120-180 mL. Under ultraviolet light initiation, excess ethanedithiol is added to the terminal double bond of the intermediate to form a thiol-terminated small molecule network compound.

[0013] Step A3: The coated modifier, dimethylacetamide and ethanol are mixed, and the MXene nanosheets are added for ultrasonic dispersion and then allowed to stand for 2 hours, and then the silver nitrate solution is added, and the water bath temperature is controlled at 60-80°C, and stirring is applied at 30-50 rpm. The reaction is carried out at a constant temperature for 8-12 hours. After the reaction is completed, the precipitate is centrifuged, washed with water and dried to obtain a silver-loaded precursor;

[0014] Furthermore, the feed ratio of MXene nanosheets, coating modifier, silver nitrate, dimethylacetamide and ethanol is 10g: 0.22-0.28g: 0.35-0.4g: 30-40mL: 15-30mL. The coating modifier molecules are rich in amide groups and are fully dispersed in the dimethylacetamide system. Its multi-amide structure forms a chelating effect with the secondary amine and thioether structure, and forms a chelating force with the active transition metal element sites on the MXene sheet, thereby enriching it on the surface of the MXene sheet. The chelating structure without active sites captures the added silver ions and is reduced to elemental silver by the thiol group.

[0015] Step A4: Place the silver-loaded precursor in a nitrogen atmosphere furnace, first bake at 420-460°C for 2.5-3h, then continue to heat up to 550-600°C and bake for 1.5-2h, and then break up after cooling in the furnace to obtain Ag / MXene micropowder; organic matter decomposes under high temperature baking, and a large number of silver clusters are formed on the surface of MXene nanosheets, increasing the contact probability with silver powder. The tiny silver clusters have a good buffering effect, are not easily destroyed during the deformation process, maintain stable conductivity, and the amount of silver used is lower than that of traditional silver-coated products.

[0016] Furthermore, the thixotropic agent is oleophilic fumed silica, which adjusts the thixotropic properties of the conductive silver paste and imparts it with good printability.

[0017] Furthermore, the organic resin is a polyurethane resin, which can be cured at low temperature, has good printability before curing, and has stable adhesion after curing.

[0018] Furthermore, the curing agent is an oxazolidine latent curing agent, which cooperates with the polyurethane resin to maintain good printability.

[0019] A method for preparing a high-performance conductive silver paste comprises the following steps: premixing and dissolving an organic resin and a solvent, and then adding other raw materials to grind and slurry to obtain the conductive silver paste.

[0020] Beneficial effects of the present invention:

[0021] The invention is based on a traditional conductive silver paste system, with polyurethane resin as a bonding material, silver powder as a basic conductive material, and independently developed Ag / MXene micropowder compounded. The obtained paste has low resistivity after curing, and the cured line has excellent anti-flexing property. The Ag / MXene micropowder uses MXene nanosheets as carriers, and is prepared by amine ester exchange reaction of diethyl iminodiacetate and diallylamine to form a compound with a polyvalent terminal olefin group, which is an intermediate, and then a small molecule network compound capped with a thiol group is added to the terminal double bond of ethanedithiol and the intermediate, which is a coating modifier. The multi-amide structure in the network structure forms a chelating effect with the secondary amine and the thioether structure, and can form a chelating force with the active transition metal element site on the MXene sheet, and then spreads evenly on the MXene sheet, and is reduced by liquid phase. The MXene film is coated with a modified agent containing only carbon, nitrogen, oxygen and sulfur elements, which is easy to be thermally decomposed, and the decomposition products have little effect on the conductivity of MXene. The silver clusters on the surface of the MXene film act like pins, increasing the contact probability between the film structure and the silver powder. Compared with flaky conductive materials, such as flaky silver powder, graphene, etc., it is easy to form more conductive channels and improve the conductivity of the slurry after curing. In addition, the MXene film has a more suitable elastic modulus and good deformation recovery ability. The surface of the MXene film is non-coated small silver clusters, which have a good buffering effect and better structural stability during deformation, thereby maintaining stable conductivity. It has far-reaching application value in flexible conductive materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0023] Figure 1 This is an electron microscope image of the Ag / MXene micropowder prepared in Example 3 of the present invention. DETAILED DESCRIPTION

[0024] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] Example 1, preparing high-performance conductive silver paste, the specific implementation process is as follows:

[0026] (1) Preparation of Ag / MXene powder

[0027] Step A1: premix diethyl iminodiacetate, diallylamine and anhydrous toluene under dry nitrogen protection, heat to 50°C, stir at 120rpm, slowly add trimethylaluminum to react for 4h, then continue to heat and reflux for 1.5h, wherein the feed ratio of diethyl iminodiacetate, diallylamine, trimethylaluminum and anhydrous toluene is 0.1mol:0.2mol:35mg:55mL. After the reaction is completed, vacuum rotary evaporation is performed to quickly remove toluene to obtain an intermediate.

[0028] Step A2: Mix the intermediate, benzoin dimethyl ether and acetone, introduce nitrogen protection, heat to 55°C, stir at 150 rpm and apply 150 W / m 2 Under ultraviolet irradiation, take equal amounts of ethanedithiol and divide them into four parts, add them intermittently for 20 minutes, and control the addition of ethanedithiol to react for 2.5 hours. Among them, the feed ratio of intermediate, ethanedithiol, benzoin dimethyl ether and acetone is 0.1 mol: 0.32 mol: 80 mg: 180 mL. After the reaction, acetone is removed by rotary evaporation to obtain a coated modifier.

[0029] Step A3: Take the coating modifier, dimethylacetamide and ethanol and mix them, add MXene nanosheets for ultrasonic dispersion and let it stand for 2 hours, then add silver nitrate solution, control the temperature of the water bath to 80°C, apply 50rpm stirring, and react at a constant temperature for 8 hours, wherein the MXene nanosheets are selected from the commercially available XFK52 type powder raw materials, and the feed ratio of MXene nanosheets, coating modifier, silver nitrate, dimethylacetamide and ethanol is 10g:0.28g:0.4g:40mL:15mL, the concentration of the silver nitrate solution is 1mol / L, and the reaction is completed by centrifugation, the precipitate is washed with water and dried to obtain a silver-loaded precursor.

[0030] Step A4: Place the silver-loaded precursor in a nitrogen atmosphere furnace, first calcine at 460°C for 2.5 hours, then continue to heat to 600°C and calcine for 1.5 hours, and then break up after cooling in the furnace to obtain Ag / MXene micropowder.

[0031] (2) Preparation of conductive silver paste

[0032] Ingredients: raw materials are taken by weight, 30 parts of micron-grade silver powder, selected from ML-Ag-W05 raw materials; 1.9 parts of nano-grade silver powder, selected from ML-Ag-N80 raw materials; 15 parts of Ag / MXene powder, which is self-made in this embodiment; 1.8 parts of thixotropic agent, selected from VK-SP15G oleophilic fumed silica; 25 parts of organic resin, selected from 5836P polyurethane resin; 1.3 parts of curing agent, selected from TP-820 oxazolidine latent curing agent; 38 parts of solvent, selected from diethylene glycol butyl ether acetate;

[0033] Pulping: Premix and dissolve the organic resin and solvent, then add the remaining raw materials, and grind them for 15 minutes using a three-roll grinder to obtain a conductive silver paste.

[0034] Example 2, preparing high-performance conductive silver paste, the specific implementation process is as follows:

[0035] (1) Preparation of Ag / MXene powder

[0036] Step A1: premix diethyl iminodiacetate, diallylamine and anhydrous toluene under dry nitrogen protection, heat to 40°C, stir at 90rpm, slowly add trimethylaluminum to react for 5h, then continue to heat and reflux for 2h, wherein the feed ratio of diethyl iminodiacetate, diallylamine, trimethylaluminum and anhydrous toluene is 0.1mol:0.2mol:25mg:45mL. After the reaction is completed, vacuum rotary evaporation is performed to quickly remove toluene to obtain an intermediate.

[0037] Step A2: Mix the intermediate, benzoin dimethyl ether and acetone, introduce nitrogen protection, heat to 45°C, stir at 120 rpm and 100 W / m 2 Under ultraviolet irradiation, take equal amounts of ethanedithiol and divide them into four parts, add them intermittently for 20 minutes, and control the addition of ethanedithiol to react for 3.2 hours. Among them, the feed ratio of intermediate, ethanedithiol, benzoin dimethyl ether and acetone is 0.1 mol: 0.28 mol: 60 mg: 120 mL. After the reaction, acetone is removed by rotary evaporation to obtain a coated modifier.

[0038] Step A3: Take the coating modifier, dimethylacetamide and ethanol and mix them, add MXene nanosheets and ultrasonically disperse them, then let them stand for 2 hours, then add silver nitrate solution, control the temperature of the water bath to 60°C, apply stirring at 30rpm, and react at a constant temperature for 12 hours, wherein the MXene nanosheets are selected from the commercially available XFK52 type powder raw materials, and the feed ratio of MXene nanosheets, coating modifier, silver nitrate, dimethylacetamide and ethanol is 10g:0.22g:0.35g:30mL:30mL, the concentration of silver nitrate solution is 1mol / L, and the reaction is completed by centrifugation, the precipitate is washed with water and dried to obtain a silver-loaded precursor.

[0039] Step A4: Place the silver-loaded precursor in a nitrogen atmosphere furnace, first calcine at 420°C for 3 hours, then continue to heat up to 550°C and calcine for 2 hours, and then break up after cooling in the furnace to obtain Ag / MXene micropowder.

[0040] (2) Preparation of conductive silver paste

[0041] Ingredients: raw materials are taken by weight, 40 parts of micron-grade silver powder, selected from ML-Ag-W05 raw materials; 2.7 parts of nano-grade silver powder, selected from ML-Ag-N80 raw materials; 22 parts of Ag / MXene powder, which is self-made in this embodiment; 2.4 parts of thixotropic agent, selected from VK-SP15G oleophilic fumed silica; 35 parts of organic resin, selected from 5836P polyurethane resin; 1.8 parts of curing agent, selected from TP-820 oxazolidine latent curing agent; 52 parts of solvent, selected from diethylene glycol butyl ether acetate;

[0042] Pulping: Premix and dissolve the organic resin and solvent, then add the remaining raw materials, and grind them for 15 minutes using a three-roll grinder to obtain a conductive silver paste.

[0043] Example 3, preparing high-performance conductive silver paste, the specific implementation process is as follows:

[0044] (1) Preparation of Ag / MXene powder

[0045] Step A1: premix diethyl iminodiacetate, diallylamine and anhydrous toluene under the protection of dry nitrogen, heat to 45°C, stir at 120rpm, slowly add trimethylaluminum to react for 4.2h, and then continue to heat and reflux for 1.8h, wherein the feed ratio of diethyl iminodiacetate, diallylamine, trimethylaluminum and anhydrous toluene is 0.1mol:0.2mol:30mg:50mL. After the reaction is completed, the toluene is quickly removed by reduced pressure rotary evaporation to obtain an intermediate.

[0046] Step A2: Mix the intermediate, benzoin dimethyl ether and acetone, introduce nitrogen protection, heat to 50°C, stir at 150 rpm and 120 W / m 2 Under ultraviolet irradiation, take equal amounts of ethanedithiol and divide them into four parts, add them intermittently for 20 minutes, and control the addition of ethanedithiol to react for 3 hours, wherein the feed ratio of the intermediate, ethanedithiol, benzoin dimethyl ether and acetone is 0.1 mol: 0.3 mol: 70 mg: 150 mL. After the reaction, the acetone is removed by rotary evaporation to obtain a coated modifier.

[0047] Step A3: Take the coating modifier, dimethylacetamide and ethanol and mix them, add MXene nanosheets and ultrasonically disperse them, then let them stand for 2 hours, then add silver nitrate solution, control the temperature of the water bath to 70°C, apply 50rpm stirring, and react at a constant temperature for 10 hours, wherein the MXene nanosheets are selected from the commercially available XFK52 type powder raw materials, and the feed ratio of MXene nanosheets, coating modifier, silver nitrate, dimethylacetamide and ethanol is 10g:0.24g:0.35g:40mL:20mL, the concentration of the silver nitrate solution is 1mol / L, and the reaction is completed by centrifugation, the precipitate is washed with water and dried to obtain a silver-loaded precursor.

[0048] Step A4: Place the silver-loaded precursor in a nitrogen atmosphere furnace, first calcine at 450°C for 3 hours, then continue to heat to 580°C and calcine for 1.7 hours, and then break up after cooling in the furnace to obtain Ag / MXene micropowder.

[0049] (2) Preparation of conductive silver paste

[0050] Ingredients: raw materials are taken by weight, 35 parts of micron-grade silver powder, selected from ML-Ag-W05 raw materials; 2.4 parts of nano-grade silver powder, selected from ML-Ag-N80 raw materials; 20 parts of Ag / MXene powder, which is prepared in this embodiment; 2.2 parts of thixotropic agent, selected from VK-SP15G oleophilic fumed silica; 30 parts of organic resin, selected from 5836P polyurethane resin; 1.6 parts of curing agent, selected from TP-820 oxazolidine latent curing agent; 45 parts of solvent, selected from diethylene glycol butyl ether acetate;

[0051] Pulping: Premix and dissolve the organic resin and solvent, then add the remaining raw materials, and grind them for 15 minutes using a three-roll grinder to obtain a conductive silver paste.

[0052] Comparative Example 1, referring to Example 3, the Ag / MXene powder was replaced with the same weight portion of ML-Ag-PW10 type flaky silver powder, and the rest of the implementation process was exactly the same.

[0053] Comparative Example 2, referring to Example 3, the Ag / MXene powder was replaced with the same weight portion of XFDZ151 type nanosilver modified reduced graphene oxide, and the rest of the implementation process was exactly the same.

[0054] The conductive silver paste prepared above was screen-printed on a PET substrate using a 300-mesh nylon brush, with a line printing size of 0.4 mm × 100 mm, and cured at 120° C. for 2 h to obtain a sample;

[0055] The resistivity of the line is tested using a four-probe tester and recorded as the initial resistivity ρ 0 ; According to the YS / T 606-2006 standard, the sample was folded 180° perpendicular to the length direction, pressed flat with 2kg for 10 minutes, and bent repeatedly 50 times. The resistivity of the line was tested again, which was recorded as the bending resistivity ρ 1 ; Calculate the resistance increase rate Φ=(ρ 1 -ρ 0 ) / ρ 0 ×100%; the specific test data are shown in Table 1:

[0056] Table 1

[0057] Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 <![CDATA[ρ 0 / Ω·cm]]> <![CDATA[4.27×10 -5 ]]> <![CDATA[4.07×10 -5 ]]> <![CDATA[3.92×10 -5 ]]> <![CDATA[5.83×10 -5 ]]> <![CDATA[4.67×10 -5 ]]> Φ / % 3.10 2.51 2.73 3.74 8.42

[0058] It can be seen from the test results in Table 1 that the conductive silver paste prepared in the embodiment has extremely low resistivity after curing, and has a low resistance increase rate after bending, showing excellent flexural resistance, and has far-reaching application value in flexible conductive materials.

[0059] Based on the test results in Table 1 above, the Ag / MXene powder prepared in Example 3 was observed by electron microscopy. Figure 1 As shown, it is lamellar with a large number of silver clusters attached to the surface.

[0060] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

Claims

1. A high performance conductive silver paste, characterized in that: The composition includes, by weight: 30-40 parts of micron-sized silver powder, 1.9-2.7 parts of nano-sized silver powder, 15-22 parts of Ag / MXene powder, 1.8-2.4 parts of thixotropic agent, 25-35 parts of organic resin, 1.3-1.8 parts of curing agent and 38-52 parts of solvent; The Ag / MXene powder is prepared by the following method: Step A1: premix diethyl iminodiacetate, diallylamine and anhydrous toluene under dry nitrogen protection, heat to 40-50°C, stir and slowly add trimethylaluminum to react for 4-5h, then continue to heat and reflux for 1.5-2h, and quickly remove toluene by vacuum rotary evaporation to obtain an intermediate; Step A2: Mix the intermediate, benzoin dimethyl ether and acetone, introduce nitrogen protection, heat to 45-55°C, stir and apply 100-150W / m 2 UV irradiation, intermittently adding ethanedithiol to react for 2.5-3.2 hours, after the reaction is completed, acetone is removed by rotary evaporation to obtain a coated modifier; Step A3: The coated modifier, dimethylacetamide and ethanol are mixed and dissolved, MXene nanosheets are added for ultrasonic dispersion, and then the mixture is allowed to stand for 2 hours. Then, a silver nitrate solution is added, and the temperature of the water bath is controlled at 60-80°C. The mixture is stirred and reacted at a constant temperature for 8-12 hours. After the reaction is completed, the precipitate is centrifuged, washed with water and dried to obtain a silver-loaded precursor. Step A4: Place the silver-loaded precursor in a nitrogen atmosphere furnace, first calcine at 420-460°C for 2.5-3h, then continue to heat to 550-600°C and calcine for 1.5-2h, and then break up after cooling in the furnace to obtain Ag / MXene micropowder.

2. The high performance conductive silver paste according to claim 1, characterized in that: The feed ratio of diethyl iminodiacetate, diallylamine, trimethylaluminum and anhydrous toluene is 0.1 mol: 0.2 mol: 25-35 mg: 45-55 mL.

3. The high performance conductive silver paste according to claim 2, characterized in that: The feed ratio of the intermediate, ethanedithiol, benzoin dimethyl ether and acetone is 0.1 mol: 0.28-0.32 mol: 60-80 mg: 120-180 mL.

4. The high performance conductive silver paste according to claim 3, characterized in that: The feed ratio of MXene nanosheets, coating modifier, silver nitrate, dimethylacetamide and ethanol is 10g: 0.22-0.28g: 0.35-0.4g: 30-40mL: 15-30mL.

5. The high performance conductive silver paste according to claim 1, characterized in that: The thixotropic agent is oleophilic fumed silica.

6. The high performance conductive silver paste according to claim 1, characterized in that: The organic resin is polyurethane resin.

7. The high performance conductive silver paste according to claim 1, characterized in that: The curing agent is an oxazolidine latent curing agent.

8. A method for preparing a high-performance conductive silver paste according to any one of claims 1 to 7, characterized in that: Specifically, the organic resin and the solvent are premixed and dissolved, and then the remaining raw materials are added and ground into a slurry to obtain a conductive silver slurry.

Citation Information

Patent Citations

  • Meshed two-dimensional flake silver powder and liquid phase synthesis method thereof

    CN105268992A

  • Nano platinum / carbon nanotube / MXene fiber composite material and preparation method and application thereof

    CN117758505A

  • Silver powder and conductive paste, conductive coating and conductive sheet using the same

    JP2017071819A

  • High loadings of silver nanowires: dispersions and pastes; conductive materials; and corresponding methods

    US20240343923A1

  • Two-dimensional particle-containing composition and production method for two-dimensional particle-containing composition

    WO2024185855A1